2018
DOI: 10.1089/ten.tea.2018.0013
|View full text |Cite
|
Sign up to set email alerts
|

Sclerostin-Neutralizing Antibody Enhances Bone Regeneration Around Oral Implants

Abstract: These results indicate that systemic Scl-Ab administration enhances osseointegration and bone regeneration around dental implants. This approach offers potential as a treatment modality for patients with low bone mass or bone defects to achieve more predictable bone regeneration at alveolar bone defects and to enhance dental implant osseointegration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
35
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(37 citation statements)
references
References 41 publications
1
35
0
Order By: Relevance
“…The findings from this investigation demonstrate that systemically-administered Scl-Ab was associated with improved osseous repair of large alveolar bone defects in comparison with the effects of local Scl-Ab formulated in PLGA microspheres, microspheres alone, or no treatment. These findings build on the large body of evidence demonstrating that systemic Scl-Ab therapy stimulates new bone formation and increased alveolar bone volume and density following experimental periodontitis and around large bone defects at the time of dental implant placement 21,23,31 . These results suggest therapeutic potential for this approach in a variety of dental applications.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…The findings from this investigation demonstrate that systemically-administered Scl-Ab was associated with improved osseous repair of large alveolar bone defects in comparison with the effects of local Scl-Ab formulated in PLGA microspheres, microspheres alone, or no treatment. These findings build on the large body of evidence demonstrating that systemic Scl-Ab therapy stimulates new bone formation and increased alveolar bone volume and density following experimental periodontitis and around large bone defects at the time of dental implant placement 21,23,31 . These results suggest therapeutic potential for this approach in a variety of dental applications.…”
Section: Discussionmentioning
confidence: 53%
“…Considering the unique characteristics of Scl-Ab for the promotion of bone density in a variety of contexts, several studies have reported the ability of Scl-Ab to address unmet dental needs. Scl-Ab administration has previously shown inhibition of periodontal disease progression 32 , enhancement of the recovery from periodontal disease 21 , and increased osteointegration and bone regeneration around dental implants 23 . Moreover, in two large clinical studies, a single case of osteonecrosis of the jaw (ONJ) bone was reported 17,18,31,32 whereas antiresorptive agents including bisphosphonates and denosumab are associated with an increased risk of ONJ.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 67 , 68 ] In addition, Scl-Ab administration can enhance osseointegration and bone regeneration around bone implant and dental implants, which indicates a potential therapeutic approach to reduce the healing time and accelerate bone regeneration after implant placement. [ 69 , 70 ] Moreover, an animal experiment in 2018 proved that treatment with Scl-Ab significantly increased mandibular bone mass and alveolar height in wild-type mice. [ 63 ] Use of Scl-Ab is a prospective treatment method for bone absorption induced by periodontitis and other oral therapies like orthodontic or implant treatment.…”
Section: Anti-sclerostin Antibodiesmentioning
confidence: 99%
“…This research needs to be guided by an appropriate understanding of the cell biological mechanisms underlying pathological changes and regeneration in the oral tissue, including the periodontium and the dental tissue. Due to the major role of Wnt signaling and the respective regulators in development and healing, research in regenerative medicine and dentistry has evaluated the feasibility of targeting the pathway for therapeutic approaches ( Florio et al ., 2016; Heiland et al ., 2010; Taut et al ., 2013; Yu et al ., 2018).…”
Section: Introductionmentioning
confidence: 99%